The First Report of Robotic Bilateral Modified Radical Neck Dissection Through the Bilateral Axillo-breast Approach for Papillary Thyroid Carcinoma With Bilateral Lateral Neck Metastasis. Issue 3 (June 2020) - Song, Ra-Yeong; Sohn, Hee Ju; Paek, Se Hyun; Kang, Kyung Ho
Abstract : Background: Robotic unilateral modified radical neck dissection (MRND) has been reported to be safe and achieves good oncologic results. However, there is no report of successful robotic bilateral MRND to date. We report the first case series of robotic bilateral MRND through the bilateral axillo-breast approach (BABA). Methods and Results: We reviewed 4 patients who presented with papillary thyroid cancer and metastasis to both lateral neck compartments. BABA robotic total thyroidectomy with bilateral MRND was performed. There were no incidences of vocal cord palsy, permanent hypoparathyroidism, or chyle leakage. All patients underwent high-dose radioiodine ablation. At last follow-up, imaging tests showed no recurrence and thyroglobulin levels remained low. Conclusions: BABA allows complete compartment-oriented neck dissection with outcomes that may be comparable with open bilateral MRND. BABA robotic surgery could be a good alternative for patients with papillary thyroid cancer and bilateral neck metastasis who wish to avoid long neck scar.